HIV Pre-Exposure Prophylaxis: Scoping Review (Research, Society and Development, 2023)
Introduction: The lack of provision of HIV pre-exposure prophylaxis in medication dispensing units means that populations eligible for the use of prophylaxis are deprived of access, contributing to an increased risk of acquiring the HIV virus. Objective: To map potential strategies for pharmaceutical services and/or pharmaceutical care for Pre-exposure Prophylaxis to the Human Immunodeficiency Virus. Methodology: Scope review guided by the acronym PCC, where Participants: Pharmacists; Concept: Pre-exposure prophylaxis to the Human Immunodeficiency Virus; Context: Medium Complexity Health Care. Results: There are records that pharmaceutical services and/or pharmaceutical care for Pre-exposure Prophylaxis to the Human Immunodeficiency Virus reduce new cases of HIV, as does the offer of PrEP by pharmaceutical professionals. Conclusion: The findings show that pharmaceutical services and/or pharmaceutical care for Pre-exposure Prophylaxis to the Human Immunodeficiency Virus are robust.